Penelitian Energi Terbarukan di Pedesaan dalam 20 Tahun Terakhir: Sebuah Bibliometik Analisis - Adhityo Nugraha Barsei; Andreo Wahyudi Atmoko (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2023)
Renewable energy is currently an alternative to reducing the use of fossil energy. In addition, renewable energy also has the benefits of increasing electrification in remote or rural areas. Many researchers have carried out various studies on renewable energy. However, research on renewable energy in remote or rural areas is rarely conducted. This study analyzes the scientific literature to find the most influential trending publications, author articles, journals, and countries on rural renewable energy research. This study used a bibliometric methodology using data from the Scopus database from 2003 to 2022. Data visualization and analysis used biblioshiny and then exported using excel and the VOSviewer application. The research results yielded several main findings, 1) The publication of research on renewable energy in rural areas has increased significantly from 2011 to 2022; 2) Journal of Energy for Sustainable Development is the most influential journal in terms of the number of sites, publications, and most influential articles; 3) Writers and academics from developed countries are more productive than developing countries in producing scientific articles on renewable energy in rural areas; 4) The keywords rural development, developing countries, and energy transition are research topics that are rarely carried out and may become future research topics.